Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s00280-009-1217-0
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled phase II comparison study of concurrent chemoradiotherapy with docetaxel, cisplatin, and 5-fluorouracil versus CCRT with cisplatin, 5-fluorouracil, methotrexate and leucovorin in patients with locally advanced squamous cell carcinoma of the head and neck

Abstract: We compared concurrent chemoradiotherapy (CCRT) with docetaxel, cisplatin (CDDP), and 5-fluorouracil (5-FU) (TPF) with CCRT with CDDP, 5-FU, methotrexate and leucovorin (PFML) in patients with locally advanced squamous cell carcinoma of the head and neck (SCCHN) in terms of safety and efficacy on survival. A total of 100 patients were enrolled. The TPF group received CCRT with the TPF regimen [docetaxel (50 mg/m(2): day 1), CDDP (60 mg/m(2): day 4), and continuous 5-FU infusion (600 mg/m(2)/day: days 1-5)]. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Although the results of the outcomes in this study support the findings of previous reports (Shaha et al 1984;Hicks et al 1997;Sessions et al 2000), we emphasize that the patient outcome for surgery in our patients was almost equal to, or better than those of previous reports (Hicks et al 1997;Sessions et al 2000;Diaz et al 2003) and this study contained some intensive CRT patients, such as iaCDDP (Doweck et al 2008), CF (Giralt et al 2000), and DCF (Tsukuda et al 2010).…”
Section: Discussionsupporting
confidence: 59%
“…Although the results of the outcomes in this study support the findings of previous reports (Shaha et al 1984;Hicks et al 1997;Sessions et al 2000), we emphasize that the patient outcome for surgery in our patients was almost equal to, or better than those of previous reports (Hicks et al 1997;Sessions et al 2000;Diaz et al 2003) and this study contained some intensive CRT patients, such as iaCDDP (Doweck et al 2008), CF (Giralt et al 2000), and DCF (Tsukuda et al 2010).…”
Section: Discussionsupporting
confidence: 59%
“…Due to the anatomical features of the head and neck, organ preservation is important to maintain functions and to minimize aesthetic changes. To preserve function, some authors have described the efficacy of chemoradiotherapy (CRT) and neo-adjuvant (induction) chemotherapy followed by definitive radiotherapy for advanced HNSCC patients [1][2][3][4][5][6][7][8][9][10][11]. Until recently, planned neck dissection (PND) after CRT was a common treatment method for lymph node(s) metastatic advanced HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…Posner et al [6] reported that TPF after carboplatin-CRT provided significantly better 2-year overall survival for resectable and We have performed phase I and II studies of TPF-CRT and observed a CR rate of 90 % and a 3-year survival rate of 95.8 %, although the incidences of grades 3-4 mucositis, leukocytopenia, and neutropenia were 79, 53, and 42 %, respectively [7,8]. These severe adverse events could lead to treatment discontinuation, which indicates that a more tolerable alternative is needed.…”
Section: Discussionmentioning
confidence: 95%
“…Based on our results for TPF-CRT [7,8], and the substitution of Cmab for 5-FU, we expected that B-CRT using DTX and CDDP plus Cmab would produce a <50 % incidence of grades 3-4 neutropenia. Therefore, we defined the expected incidence of neutropenia as 50 %, the threshold incidence of neutropenia as 77 %, the alpha error as 0.1, and the beta error as 0.1.…”
Section: Patientsmentioning
confidence: 97%
See 1 more Smart Citation